Recurrent impetigo herpetiformis successfully treated with methotrexate: A case report - Luewan S. (2014)
Impetigo herpetiformis is a rare disease and its occurrence is specific for pregnancy. The lesions are characterized by sterile, pustular eruptions. The disorder is usually seen in the third trimester, but cases of impetigo herpetiformis appearing in the first trimester have also been reported. The lesions are expected to disappear after birth, but the disorder may recur during subsequent pregnancies. In this case report we discuss a 28-year-old pregnant woman, G3P1011, with a history of impetigo herpetiformis in the first pregnancy, who presented with generalized pustular lesions at 30 weeks' gestation. Her disease responded poorly to corticosteroids and was more severe than in the previous pregnancy. She delivered prematurely at 34 weeks' gestation and then received aggressive postpartum treatment with methotrexate, resulting in a dramatic response. This case supports the current understanding that recurrent impetigo herpetiformis in subsequent pregnancy tends to be more severe and to have an earlier onset. Additionally, it provides additional evidence that methotrexate may be used as an alternative treatment for impetigo herpetiformis in the case of a poor response to corticosteroids. © 2010 The Authors.